Charge doping to flat AgF2 monolayers in a chemical capacitor setup. Issue 26 (17th May 2022) - Jezierski, Daniel; Grzelak, Adam; Liu, Xiaoqiang; Pandey, Shishir Kumar; Gastiasoro, Maria N.; Lorenzana, José; Feng, Ji; Grochala, Wojciech
Abstract : Flat monolayers of silver(ii ) fluoride have been recently predicted to have large potential for ambient pressure superconductivity if doped to an optimal level. Here we calculate how much optimal level is and explore chemical ways of doping. Abstract : Flat monolayers of silver(ii ) fluoride, which could be obtained by epitaxial deposition on an appropriate substrate, have been recently predicted to exhibit very strong antiferro-magnetic superexchange and to have large potential for ambient pressure superconductivity if doped to an optimal level. It was shown that AgF2 could become a magnetic glue-based superconductor with a critical superconducting temperature approaching 200 K at optimum doping. In the current work we calculate the optimum doping to correspond to 14% of holes per formula unit, i.e. quite similar to that for oxocuprates(ii ). Furthermore, using DFT calculations we show that flat [AgF2 ] single layers can indeed be doped to a controlled extent using a recently proposed "chemical capacitor" setup. Hole doping associated with the formation of Ag(iii ) proves to be difficult to achieve in the setup explored in this work as it falls at the verge of charge stability of fluoride anions and does not affect the d( x 2 − y 2 ) manifold. However, in the case of electron doping, manipulation of different factors – such as the number of dopant layers and the thickness of the separator – permits fine tuning of the doping level (and concomitantly T C ) all the way from the underdoped to overdoped regime (in a similar manner to chemical doping for the Nd2 CuO4 analogue).